Reduction of Posttraumatic Stress Disorder (PTSD) Symptoms in PTSD and Major Depressive Disorder Comorbidity After Acute Hypoglycemia—A Case Report - Pawlowski, Tomasz; Daroszewski, Jacek; Czerwinska, Agnieszka; Rymaszewska, Joanna (Frontiers in Psychiatry, 2019)
Background: Approximately half of all patients with Posttraumatic Stress Disorder (PTSD) also suffer from Major Depressive Disorder (MDD). This co-occurrence might lead to an impairment of cognitive functions, worse response to antidepressant medications and an increased risk of suicide in comparison to patients with PTSD alone. Prognosis for people with PTSD and MDD co-occurrence is poorer than for either one alone, therefore researchers look for novel, effective treatments. Case presentation: A patient with MDD with the co-occurrence of PTSD was admitted to the Department of Endocrinology with suspicion of adrenal insufficiency. In order to assess the adrenocorticotropin/cortisol axis a standard insulin tolerance test was performed. After inducing a hypoglycaemic episode with intravenous short-acting insulin, PTSD symptoms were reduced. To the best of our knowledge, this is the first report on the reduction of PTSD symptoms after performing an insulin tolerance test. Conclusion: Reduction of PTSD symptoms in PTSD and MDD comorbidity has been noticed after a hypoglycaemic episode. This demonstrates the mutual dependencies between the endocrine and nervous systems, covered extensively by psychoneuroendocrinology.